Prostatic adenocarcinoma presenting with metastases to the testis and epididymis: A case report - ZHANG, JIN (Oncol Lett, 2016)
Few cases of testicular metastases from prostate carcinoma have been reported, and asymptomatic metastases of prostate carcinoma to both the testis and epididymis are extremely rare. The current study presents the case of a 69-year-old male with testicular and epididymal metastases from prostate carcinoma. The patient was admitted to The First Hospital of Shijiazhuang with a 2-year history of lower urinary tract symptoms. Digital rectal examination revealed an enlarged multinodular prostate, and the serum prostate-specific antigen (PSA) level was >100 ng/ml. Magnetic resonance imaging showed prostate carcinoma with seminal vesicle involvement. A prostate biopsy showed prostate gland adenocarcinoma. The Gleason score was 3+3. The immunohistochemistry results were as follows: Prostatic acid phosphatase (+++), PSA (+++), P504s (+++), p63 (−) and cytokeratin 34βE12 (−), with a Ki-67 of ~5%. The patient was treated with a bilateral orchiectomy. The testicular pathology showed that the right testis and epididymis were invaded with metastatic adenocarcinoma. The left testis and epididymis were normal. The patient was treated with conventional flutamide endocrine therapy. At present the patient remains in a stable condition after 24 months of follow-up.